2021
DOI: 10.1242/dev.196295
|View full text |Cite
|
Sign up to set email alerts
|

MFN2 interacts with nuage-associated proteins and is essential for male germ cell development by controlling mRNA fate during spermatogenesis

Abstract: Mitochondria play a critical role in spermatogenesis and are regulated by several mitochondrial fusion proteins. However, their functional importance associated with their structure formation and mRNA fate regulation during spermatogenesis remains unclear. Here, we show that Mitofusin 2 (MFN2), a mitochondrial fusion protein, interacts with Nuage-associated proteins (including MIWI, DDX4, TDRKH, and GASZ). Conditional mutation of Mfn2 in postnatal germ cells results in male sterility due to germ cell developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
(108 reference statements)
3
16
0
Order By: Relevance
“…When spermatocytes are deficient in MFN2, then they cannot continue to the pachytene stage and this leads to apoptosis, which ultimately results in the death of both the spermatocytes and spermatogonia in the seminiferous tubule, hence the empty appearance of this region in our histology sections. A similar phenotype has previously been reported in other studies ( Varuzhanyan et al, 2019 ; Chen et al, 2020 ; Wang et al, 2021 ), but to our knowledge, our data are the first to show details of disrupted meiosis in MFN2 deficient spermatocytes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When spermatocytes are deficient in MFN2, then they cannot continue to the pachytene stage and this leads to apoptosis, which ultimately results in the death of both the spermatocytes and spermatogonia in the seminiferous tubule, hence the empty appearance of this region in our histology sections. A similar phenotype has previously been reported in other studies ( Varuzhanyan et al, 2019 ; Chen et al, 2020 ; Wang et al, 2021 ), but to our knowledge, our data are the first to show details of disrupted meiosis in MFN2 deficient spermatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, RAB7 was shown to regulate the phosphorylation of DRP1 and thus control mitochondrial dynamics during oocytogenesis ( Pan et al, 2020 ). In addition to DRP1, several studies demonstrated that the conditional knock-out of mitofusin 1 or 2 (MFN1 or MFN2) leads to male or female infertility in mice models ( Varuzhanyan et al, 2019 ; Zhang et al, 2019 ; Chen et al, 2020 ; Wang et al, 2021 ). However, the underlying molecular mechanism responsible for this phenotype remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In undifferentiated spermatogonia, mitochondria are generally small and fragmented. As spermatogonia differentiate into spermatocytes and initiate meiosis, their mitochondria undergo mitofusin-mediated fusion to fuel meiosis ( Chen et al, 2020 ; Varuzhanyan et al, 2019 ; Wang et al, 2021 ; Zhang et al, 2016 ). In post-meiotic spermatids, acute mitochondrial fragmentation mediated by mitochondrial fission factor (MFF) generates small mitochondrial spheres, which enables their organization into a spiral array within the midpiece ( Varuzhanyan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The other portion of the daughter cells differentiate to form Type A spermatogonia and Type B spermatogonia [ 96 ], thus allowing meiosis. To investigate the effects of Mfns in the self-renewal and differentiation of SSCs, many studies have knocked out Mfns or inhibited the expression of Mfns [ 24 , 97 ]. Interestingly, the depletion of Mfn1 and Mfn2 does not influence the self-renewal of SSCs; instead, this inhibits the differentiation of SSCs (Fig.…”
Section: Mfns In the Development Of Germ Cells And Embryosmentioning
confidence: 99%